2018
DOI: 10.31219/osf.io/reahy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

kinetic manuscript

Abstract: 27Phosphorus (P) is present in diets either as naturally occurring P from raw materials or added 28 as an inorganic salt, however little is known about postprandial kinetics of P absorption in cats. 29Here we describe several studies quantifying postprandial kinetics following the ingestion of 30 diets of varying composition. Briefly, cats were fed a meal consisting of 50% of their metabolic 31 energy requirement in a randomized crossover design. A pre-meal baseline blood sample was 32 taken via cephalic cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…This would largely corroborate the current understanding of regulatory mechanisms involved in P homeostasis (43) . PTH responses in cats do appear to be more rapid than FGF-23, as indicated by post-prandial profiles observed following acute feeding studies (7) , Feeding the control diet prior to baseline sampling decreased total serum Ca significantly compared to screening values (by ~ 0.2mmol.L), it is not known whether there was a concomitant decrease in iCa as it was not measured at screening. However, all diet groups subsequently increased in Ca concentration during the test period, returning to screening levels.…”
Section: Mineral Metabolism and Regulatory Mechanismsmentioning
confidence: 90%
See 3 more Smart Citations
“…This would largely corroborate the current understanding of regulatory mechanisms involved in P homeostasis (43) . PTH responses in cats do appear to be more rapid than FGF-23, as indicated by post-prandial profiles observed following acute feeding studies (7) , Feeding the control diet prior to baseline sampling decreased total serum Ca significantly compared to screening values (by ~ 0.2mmol.L), it is not known whether there was a concomitant decrease in iCa as it was not measured at screening. However, all diet groups subsequently increased in Ca concentration during the test period, returning to screening levels.…”
Section: Mineral Metabolism and Regulatory Mechanismsmentioning
confidence: 90%
“…In mice, it was found that administration of 5µg of purified human full length FGF-23 reduced serum phosphate, PTH and calcitriol at various timepoints during the 24 hour sampling period (43) . Previous work investigating the acute responses of a high oral dose of highly soluble dietary P in cats, found that FGF-23 didn't change over a 6 hour sampling period, whereas PTH and plasma P did (7) . This could indicate that, although the timeframes are not the same, the broad mechanisms by which FGF-23 plays a role in the regulation of P may be similar, as serum P and calcitriol were found to be reduced in cats fed the moderate test diet from week 12 onwards.…”
Section: Mineral Metabolism and Regulatory Mechanismsmentioning
confidence: 93%
See 2 more Smart Citations
“…Dietary phosphorus (P) concentrations have received increased focus as a contributing factor in accelerating kidney disease (2; 3) . Studies in cats investigating postprandial appearance of P in plasma showed that diets incorporating highly soluble forms of P induced dose-dependent increases in P concentration as well as the calcium (Ca) and P regulatory parathyroid hormone (PTH) (4) . At the highest inclusion of highly soluble P tested, there was also a significant reduction in whole blood ionized calcium (iCa) (4) .…”
Section: Introductionmentioning
confidence: 99%